Calcifying Epithelial Odontogenic Tumor: A Case Report - Kundi, Jawad Ahmad; Ilyas, Muhammad; Khan, Salman; Gul, Faryal; Umar, Muhammad (Journal of Gandhara Medical and Dental Science, 2016)
ABSTRACT Calcifying epithelial odontogenic tumor (CEOT) is a rare odontogenic tumor, accounts 0.4% to 3 % of all odontogenic tumors arising from odontogenic epithelium. Dr. Jens JorgenPindborg first described this unusual lesion; subsequently Shafer et al coined the term Pindborg tumor. It occurs most commonly in the 4th to 6th decade and bears no gender predilection. A case of CEOT in a 55 years old female extending from themesial aspect of right lower canine to the contralateral third molar region is described.